Germination, regeneration and pigment detection in nelumbo nucifera gaertn. (pink Asian lotus) / Noraini Binti Mahmad - Mahmad, Noraini (2012)
In vivo and in vitro germination of three types of seeds including matured (black), immature or fruits (green) and young (yellow) of Nelumbo nucifera Gaertn. (pink Asian lotus) were done. The black and green seeds both gave the highest responses to technique of scarified with medium-sand paper and germinated in liquid (tap water) and solid (MS basal media) substrates. The black seeds with germination rate of 67.01±0.28% in vivo and 78.35±0.61% in vitro, while, green seed with 75.12±0.16% in vivo and 100.00% in vitro germination. The highest shoot length in seeds without cotyledon for black and green seed with 28.00±0.55 mm and 26.00±0.16 mm, respectively. The highest shoot length was in media with pH 5.5 for both black seed and green seeds and with 64.03±0.02 mm and 32.55±0.04 mm, respectively. The maximum root length for both black and green seeds was 14 mm on the 14th day with 3 green shoots and 6 white primary roots. Whilst, maximum root length for yellow seeds were on the 18th day with 3 green shoots and 6 white primary roots. For storage purposes, the optimum concentration for the formation of encapsulation matrix was 3.0% sodium alginate (NaC6H7O6). Encapsulated explants were soaked in 100 mM calcium chloride dehydrate (CaCl2.2H2O) solution for 30 minutes. Through sodium alginate encapsulated method (4±1°C), seeds germination reduced from 100% (day 1) to 53.3±1.2% (day 90), while, through frozen whole seeds method (-20±1°C), 100% germination rate until 60 days in storage. After 90 days in storage, the germination rate was still high with 93.3±0.6%. Direct regeneration of Nelumbo nucifera Gaertn. were successfully achieved from green seed explants cultured on solid MS media supplemented with combinations of 1.5 mg/l BAP and 0.5 mg/l NAA with 10.33 ±0.23 shoots per explant (true-to-type), and with 3.67 ±0.31 roots per explant. Direct regeneration of Nelumbo nucifera Gaertn. were successfully achieved from yellow seed explants cultured on solid MS media supplemented with combinations of 0.5 mg/l BAP and 1.5 mg/l NAA with 16.00±0.30 shoots per explant, with new characteristics of layered multiple shoots. Roots were formed on solid MS basal media. Some formation of abnormal shoots (pinkish, red and oval leaf) occurred from green seed explants on solid MS media supplemented with combinations of 1.0 mg/l BAP and 2.5 mg/l NAA, 2.5 mg/l BAP and 2.5 mg/l NAA, 1.5 mg/l BAP and 2.0 mg/l NAA and 1.5 mg/l BAP and 2.5 mg/l NAA. Furthermore, the highest shoots per explant for green seed explants was in 8.8mg/l MS powder (double strength) with mean 19.03±0.05 shoots per explant. The highest shoots per explants for yellow seed explants was on 4.4 mg/l MS powder (full strength) with mean 16.06±0.06 shoots per explant. Media with pH 5.5 resulted in the highest height of shoots for green and yellow seed explants with mean 12.04±0.7 mm and 16.03±0.30 mm, respectively. While, the highest height of shoots for green seed explants with 9.41±1.11 mm in 250.00 mm light distance. The highest height of shoots with 16.67±0.23 mm for yellow seed explants in 200.00 mm light distance. Solid MS basal media was optimum for root formation within 4 weeks for green seed explants and after 24 weeks for yellow seed explants on solid MS media supplemented with 0.5mg/l BAP and 1.5mg/l NAA. In double layer media, the highest number of shoots per explant was both in ratio liquid to solid 2:1 with mean 16.67±0.23 number of shoots per explant with formation of primary and secondary roots for explants from yellow seeds with formation of layered multiple shoots, while mean 9.00±0.15 number of shoots per explant for green seeds. Extraction from lotus stamen was analyzed through HPLC system. Pigment detected was found to have the total carotenoid content of 526.96 ± 0.52 μg/g DW, whereas for individual carotenoid β-carotene (460 ± 10.28 μg/g DW) was found with a relatively high concentration and neoxanthin (39.26 ± 0.82 μg/g DW) was found in lower concentrations. One unknown carotenoid also was detected. For coating experiments, at room temperature with acidic conditions (pH 1-6), yellow pigment changed to the darker colour, yellow-brown, while, at strong alkaline condition (pH 12-14), the colour change to yellow-green. The optimum yellow colour was at pH 8-10. The highest glossiness was in 1.0ml/30.0ml v/v of pigment-resin solution with mean of 74.67±0.33°. Yellow pigment in 20% PMMA (resin) was as stable as pigment-resin added with 1% tartaric acid, coated on glass slides. In contrast, the addition of 1% citric acid reduced the carotenoid color. Extraction for antimicrobial activity from in vivo and in vitro rolled leaves showed no inhibition zone to all tested bacteria Staphylococcus aureus, Pseudomonas aeruginosa ,Bacillus cereus and E.coli. However, the highest inhibition zone was from in vivo sample for both on fungi, Fusarium sp. and Trichoderma sp. with mean 9.0±0.1 mm and with 7.3±02 mm diameters, respectively. Inhibition zone for in vitro samples were 8 times lower than in vivo with mean of 2.0±0.4 mm on Fusarium sp. and 1.1±0.3 mm on Trichoderma sp. Soil samples collected from Tasik Chini with mean pH of 3.97±0.02, while the optimum survival for acclimatization plantlets was on black clay loam (mean pH 6.03±0.29) that commercialized at all the nurseries in Malaysia. The most acidic soils were collected from Tasik Chini with the lowest survival rate (31.34±0.77%) for green seed and 11.11±0.51% for yellow seeds. The highest survival rate was in black clay loam for both plantlets from green and yellow seeds with 83.01±0.23% and 69.22±0.43%, respectively. The highest plantlets height was obtained from plant acclimatized under full sunlight exposure with 10 times from shady exposure. Acclimatized plantlets showed the same character as mother plants, even though at the beginning of transferred with layered multiple shoots (new character was formed in vitro only).